Budidaya dan analisis usahatani selada hidroponik di Tani Tirta Kelurahan Sukajaya, Kecamatan Bungursari, Kota Tasikmalaya - Sri Astuti, Yani; Saputra, Ega; Rizky Fauzan, Muhammad; Dewi Utami, Hielda; Marwah Azizah, Sopa; Maulida Ramdhani, Ajeng (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
This research aims to analyzed hydroponic lettuce cultivation at Tani Tirta, Tasikmalaya, using the Nutrient Film Technique (NFT) and Deep Flow Technique (DFT) systems in 2,000 planting holes. The research method includes purposive location selection, with observations of variables such as media type, irrigation system, production costs, and income. Primary data were obtained through in-depth interviews and field observations, while secondary data included information about location profiles and hydroponic developments. Data analysis was conducted descriptively to understand the cultivation process and business feasibility. The results showed that the main challenges in cultivation are pest attacks, weather impacts, and reliance on electricity. However, the implementation of solutions such as the construction of greenhouses and the use of backup lights successfully addressed these challenges. Economic analysis shows total production costs of IDR2,140,000.00 and total revenue of IDR3,000,000.00, with an R/C ratio of 1.40, indicating that this business is worth developing. In conclusion, hydroponic lettuce cultivation at Tani Tirta is not only economically efficient but also has the potential to contribute to local food security.